Planning Your Essay - Godwin, Janet (Basingstoke, Hampshire : Palgrave Macmillan, 2014)
This handy guide takes students through the complete process from what to do before they begin, to using feedback constructively for their next essay. Clearly and well-presented, it includes lively illustrations and now a new chapter on being critical in your essays.
Previous edition: 2009.
Includes bibliographical references and index.
Keywords: Report writing; Academic writing; Literature